The Freshwater Naiads of Ohio, Part I: St. Joseph River of the Maumee - Clarence F. Clark (Hello World!, 1977)
The lack of information on the fauna and flora of most of Ohio streams makes it difficult to evaluate the changes which have occurred in the past, and to postulate the effects of those in the future. Details pertaining to specific areas in Ohio are generally lacking in the literature but they seem to abound in the files of many Ohio scientists. The federal, state, and local governments, as well as environmental societies are alarmed at the changes which are taking and will take place with our present methods of advancing or improving our standard of living. Consequently, this paper attempts to make available data collected from the St. Joseph of the Maumee by the author and Henry Van der Schalie, and to assemble seattered published and unpublished information on that river.